Comparative analysis methods in informatics - Gasperovič, Jelena; Čaplinskas, Albertas (Lietuvos matematikos rinkinys, 2003)
The paper discusses comparative analysis methods in informatics. It examines nature of each class of methods and presents examples of its application. The purpose of the paper is to propose a classification of comparative analysis methods.